2018
DOI: 10.1002/cpmc.59
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Cryptococcus neoformans

Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen, which causes life-threatening meningoencephalitis in immunocompromised individuals and is responsible for more than 1,000,000 infections and 600,000 deaths annually worldwide. Nevertheless, anti-cryptococcal therapeutic options are limited, mainly because of the similarity between fungal and human cellular structures. Owing to advances in genetic and molecular techniques and bioinformatics in the past decade, C. neoformans, belonging to the phylum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Deletion mutant strains were constructed in the C. neoformans serotype A H99S strain background using split marker/double-joint PCR strategies [ 19 ]. The genetic information for each gene was obtained from FungiDB ( , accessed on 5 May 2018) The primers used in this study are described in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion mutant strains were constructed in the C. neoformans serotype A H99S strain background using split marker/double-joint PCR strategies [ 19 ]. The genetic information for each gene was obtained from FungiDB ( , accessed on 5 May 2018) The primers used in this study are described in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…It then disseminates to the brain via the bloodstream and infects the central nervous system by crossing the blood–brain barrier [ 17 , 18 ]. Due to the availability of its genetic mutants and molecular tools, C. neoformans has become a model species to study fungal pathogenicity and virulence mechanisms [ 19 ]. In this study, using a reverse genetic approach, we found that thymol not only induced intracellular calcium imbalance in C. neoformans but also inhibited N -glycosylation modification of the Cpy protein.…”
Section: Introductionmentioning
confidence: 99%
“…We constructed phosphatase and retromer mutant strains in the C. neoformans serotype A H99S strain background through homologous recombination using gene-disruption cassettes containing the nourseothricin-resistance marker (nourseothricin acetyl transferase; NAT ) using NAT -split marker/double joint PCR (DJ-PCR) strategies 99 (see Supplementary Data 4 for primers). We amplified 5′- and 3′-flanking regions of target genes by PCR with primer pairs L1/ L2 and R1/R2, respectively, from H99S genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous tools and resources are available for Cryptococcus sexual reproduction and genetic studies. Genetic manipulation in Cryptococcus can be achieved by biolistic transformation, Agrobacterium ‐mediated random insertional mutagenesis, or a novel CRISPR‐mediated electroporation method (Davidson et al., ; Esher, Granek, & Alspaugh, ; Fan & Lin, ; Jung, Lee, So, & Bahn, ; Toffaletti & Perfect, ; Toffaletti, Rude, Johnston, Durack, & Perfect, ). Congenic strain pairs (i.e., strains that are genetically identical with the exception of the MAT locus) have been constructed for C. neoformans , C. deneoformans , and C. deuterogattii (Heitman, Allen, Alspaugh, & Kwon‐Chung, ; Nielsen et al., ; Zhai et al., ).…”
Section: Introductionmentioning
confidence: 99%